2022
DOI: 10.4314/ejhs.v32i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Delay in reaching institutional delivery service utilization among mothers attending Jimma Medical Center, Ethiopia

Abstract: BACKGROUND: Maternal delay in the utilization of delivery services is one of the contributing factors for high maternal mortality in developing countries. However, it is preventable by timely arrival for obstetric care. The difference between life and death in obstetrics might be a matter of timely arrival and management. The objective of this study was to assess factors associated with maternal delay in reaching institutional delivery service utilization among mothers attending Jimma Medical Center.METHOD: Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In Southern Mozambique, mothers who gave birth in primary-level facilities tended to be more satisfied than those who gave birth in hospitals ( 27 ). This satisfaction might be due to the proximity of the health facility, and mothers who live a long distance from health facilities are more likely to delay reaching the hospitals on time ( 40 ). Another reason is that hospitals provide more services to patients/clients than health centers.…”
Section: Discussionmentioning
confidence: 99%
“…In Southern Mozambique, mothers who gave birth in primary-level facilities tended to be more satisfied than those who gave birth in hospitals ( 27 ). This satisfaction might be due to the proximity of the health facility, and mothers who live a long distance from health facilities are more likely to delay reaching the hospitals on time ( 40 ). Another reason is that hospitals provide more services to patients/clients than health centers.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the problem of inadequate coverage for the rural population. Studies have reported that residing in rural areas (26), far distance to health facilities (27)(28)(29), and non-availability of experienced staff (30) are significant factors limiting access to and utilization of healthcare services. A limitation of this study is that it is cross-sectional.…”
Section: Discussionmentioning
confidence: 99%